Nga Rauru : ka maro te kaki o te Kotuku : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Walsh, Michael Wehi Mailetonga (Massey University, 1992)
This thesis is concerned with the development of a resource: land, so as to provide an economic base that will sustain social and cultural activities for the iwi of Nga Rauru. Chapter One of the thesis reveals the various Acts and legislations and reasons that made land a source of conflict between Maori and Pakeha during the Nineteenth century. This is the first period of land alienation. Chapter Two highlights the Acts and legislation of the Twentieth century that continued to alienate Maori from their land. Attempts to counter this land alienation are also discussed. In Chapter Three a block of Maori land, originally Crown granted in 1882, is used to show the process of fragmentation and alienation which has produced the situation today: there is still Maori land left in the block, but it is largely leased to local Pakeha farmers. The consequences of land alienation to Maori in general, and where possible Nga Rauru specifically, is discussed in Chapter Four. Economic, cultural, spiritual, social and political factors are viewed in an attempt to gauge Nga Rauru's present 'well-being'. The final chapter calls for the utlisation of Nga Rauru lands to be returned to the iwi. A scenario concentrating on forestry development is used to indicate possible costs and returns to the iwi, in economic and social terms. The chapter concludes that there is a need for Nga Rauru to establish a Development Unit to facilitate desired economic growth for the iwi.
Keywords: New Zealand people; Maori; Land tenure; Taranaki; Ngā Rauru; History